How comparative psychology became an endangered species - Simon, Armando (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Several previous scholars have noted the decline in the field of comparative psychology in so far as fewer students are obtaining an advanced degree in the field and fewer courses are being offered in universities. However, the real cause for the decline occurred decades prior and although the problem was acknowledged at the time, no significant corrections were made and those same scholars have skirted the issue. Presently, it is bureaucratic obstacles that impede a resurgence of the discipline.